Factors influencing Corporate Investments in Public Sector and Private Sector - Alex, Dhanya; George, Sweta; Pavithran, Prof. Dr. K.B. (Journal of Contemporary Research in Management (JCRM), 2013)
This paper compares the investment behaviour of listed companies to that of observably similar privately held companies, using the dataset of fifty one Indian companies, out of which twenty five are public companies and twenty six are private companies during the period 2006 – 2010. The study also looks into the factors that influence the investment behaviour of companies which include profits earned before interest and tax, cash and bank balance and borrowings and whether the extent of influence of these factors are different in the case of public companies and private companies. It was observed that there is a significant difference in the investment behaviour of public companies and private companies.